Pemanfaatan Media Sosial untuk Pemerintahan: Bagaimana Dinas-Dinas Pemerintah Kota menggunakan Media Sosial untuk Berkomunikasi dengan Masyarakat - Khansa Nabila Ulayya; Diah Priharsari; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Social media began to be used by government agencies in Indonesia to spread information to the public. Following the establishment of Presidential degree No. 9 of 2015 on the management of public communication, government agencies have used social media as one of its communication channels.The study aims to analyze the use of government agencies' social media accounts in conducting two-way communication with the public.This is mainly to discuss how government agencies utilize social media in the digital age.Qualitative approaches with observations are taken for data collection. Data analysis uses study theory by Daniel Schlagwein 2016 for conclusions.The results indicate that social media can increase interactivity between the government and the public but the city government has not used it to its fullest.